Cancer stem cells (CSCs) in cancer progression and therapy - Najafi, Masoud; Farhood, Bagher; Mortezaee, Keywan (Journal of cellular physiology, 2019)
Cancer stem cells (CSCs) are self‐renewable cell types that are identified in most types of liquid and solid cancers and contributed to tumor onset, expansion, resistance, recurrence, and metastasis after therapy. CSCs are identified from the expression of cell surface markers, which is tumor‐type dependent. The transition between CSCs with cancer cells and other non‐CSCs occurs in cancers, which is possibly under the control of signals from CSCs and tumor microenvironment (TME), including CSC niche. Cancer‐associated fibroblasts are among the most influential cells for promoting both differentiation of CSCs and dedifferentiation of non‐CSCs toward attaining a CSC‐like phenotype. WNT/β‐catenin, transforming growth factor‐β, Hedgehog, and Notch are important signals for maintaining self‐renewal in CSCs. An effective therapeutic strategy relies on targeting both CSCs and non‐CSCs to remove a possible chance of tumor relapse. There are multiple ways to target CSCs, including immunotherapy, hormone therapy, (mi)siRNA delivery, and gene knockout. Such approaches can be designed for suppressing CSC stemness, tumorigenic cues from TME, CSC extrinsic and/or intrinsic signaling, hypoxia or for promoting differentiation in the cells. Because of sharing a range of characteristics to normal stem/progenitor cells, CSCs must be targeted based on their unique markers and their preferential expression of antigens. Most of the tumors are occupied with a number of self‐renewing cells called cancer stem cells (CSCs) that are contributed to the initiation, maintenance, and thriving cancer. The cells have rather similar characteristics to other stem cells located in the niche of body organs, but they have not essentially the same responses to the diverse stimuli. There is evidence for repopulation of CSCs after treatment with chemo/radiotherapy, which is possibly because of their highly plastic feature. Normal stem cells have the proclivity to transform into CSCs when they undergo continuous mutagenesis or receive tumorigenic signals of the tumor microenvironment (TME). Upon this transition, CSCs receive markers from their progeny. The rate of expression of these markers in CSCs is dependent on the type of tumor. CSCs can differentiate into cancer cells. In turn, cancer cells can dedifferentiate toward attaining a CSC‐like phenotype. Cancer‐associated fibroblasts provide a supportive niche for CSCs and release external cues for regulating cancer cell stemness. An effective therapeutic strategy is to target both CSCs and non‐CSCs to preclude a possible chance of tumor recurrence. Making a control over tumorigenic clues from TME or controlling intrinsic CSC signaling are optimistic approaches to break down CSC‐related tumorigenesis. Shifting CSCs from self‐renewal to differentiation can also be therapeutic through limiting their proliferative capacity, tumor recurrence, metastasis, and resistance.